Production of Reactive Oxygen Species by Photosystem II as a Response to Light and Temperature Stress - Pospíšil, Pavel (Frontiers in Plant Science, 2016)
The effect of various abiotic stresses on photosynthetic apparatus is inevitably associated with formation of harmful reactive oxygen species (ROS). In this review, recent progress on ROS production by photosystem II (PSII) as a response to high light and high temperature is overviewed. Under high light, ROS production is unavoidably associated with excitation energy transfer and electron transport in PSII. Singlet oxygen is produced by the energy transfer form triplet chlorophyll to molecular oxygen formed by the intersystem crossing from singlet chlorophyll in the PSII antennae complex or the recombination of the charge separated radical pair in the PSII reaction center. Apart to triplet chlorophyll, triplet carbonyl formed by lipid peroxidation transfers energy to molecular oxygen forming singlet oxygen. On the PSII electron acceptor side, electron leakage to molecular oxygen forms superoxide anion radical which dismutes to hydrogen peroxide which is reduced by the non-heme iron to hydroxyl radical. On the PSII electron donor side, incomplete water oxidation forms hydrogen peroxide which is reduced by manganese to hydroxyl radical. Under high temperature, dark production of singlet oxygen results from lipid peroxidation initiated by lipoxygenase, whereas incomplete water oxidation forms hydrogen peroxide which is reduced by manganese to hydroxyl radical. The understanding of molecular basis for ROS production by PSII provides new insight into how plants survive under adverse environmental conditions.